(untitled) (Heritage, 2024)
Artificial intelligence has greatly penetrated into every pore of modern society and is becoming the driver of its further development. Artificial intelligence is used in all spheres of modern life, starting from medicine, agriculture, traffic control, autonomous vehicles, smart home/building/city concepts. The paper will analyze deep learning as a branch of artificial intelligence where, by applying adequate algorithms, computers are enabled to learn independently from data. In the context of finding user behavior patterns, this technology analyzes large amounts of information to identify specific ways in which users interact with a system or services. These identified patterns are used to personalize the user experience, providing them with individualized services and improving the overall quality of the services offered. This approach allows systems to intuitively adapt their functionality to match the needs and preferences of users, leading to improved user experience and providing customers with customized services. The paper explains the concept of a "smart library", which is based on the application of the concept of deep learning in its work.